Principles of ecological zoning. (Journal of actual problems of jurisprudence, 2016)
Principles of ecological zoning are studied. The notion of sustainable development is described as a basis for ecological zoning. Significance of public participation in the process of ecological zoning is considered. Additionally, the article focuses on the economic methods that might be used in ecological zoning.
Keywords: ecological zoning; principles of ecological zoning